Representasi Makna Religius dalam Lirik Lagu “33x” Karya Band Perunggu - Latifath Ahfa, De Mimam; Ummu Salamah; Heri Hendrawan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Music becomes section of a communication process where the message conveyed in song lyrics carries a special meaning, as seen in the lyrics of the song "33x" by the band Perunggu. This song represents a religious meaning within the Islamic faith. The theory used in this research is semiotics according to Roland Barthes, which explores (1) denotative meaning, (2) connotative meaning, and (3) mythological meaning. This research applies a qualitative method using a descriptive qualitative approach. Data collection techniques include literature review, interviews, and documentation. The aim of this study is to explore the religious meaning in the lyrics of "33x" by Perunggu. The results reveal several layers of meaning: the denotative meaning, which refers to the religious act of dzikir in Islam; the connotative meaning, which suggests that "33x" carries a special significance, particularly in the Muslim faith, and from another perspective, the song also serves as a motivation and a reminder; and the mythological meaning, where the song embodies certain values that allow listeners to feel peace and be reminded of the Creator (God). Therefore, each lyric of "33x" by Perunggu holds a special meaning.